Assessment of Aedes aegypti Pupal Productivity during the Dengue Vector Control Program in a Costal Urban Centre of São Paulo State, Brazil. (3rd November 2014) - de Brito Arduino, Marylene
Abstract : The control of dengue relies on the elimination of vector breeding sites. This study identified the container categories most productive for A. aegypti within the framework of the São Paulo dengue vector control program (DVCP) in São Sebastião, a large city located on the state's coast where dengue cases have occurred since 2001. Containers were inspected monthly for the occurrence of mosquito immature stages during two consecutive vector-breeding seasons in 2002–2004. Containers were classified by their material, use, and fixed or removable status. Pupal productivity differed significantly among container types, items made of metal and plastic, and boats being those with the highest relative contribution. Significant correlations between traditional indices of A. aegypti abundance (Container Index, House Index, and Breteau Index) and pupal productivity/demographic indices (Pupae/Container, Pupae/House, Pupae/ha, and Pupae/Person) ranged 0.56–0.65; correlations were not statistically significant for any combination involving the Pupae/Container index. The assessment of pupal productivity indices could be incorporated into the DVCP without any additional operational onus, allowing vector control managers to determine appropriate control actions targeting the most productive containers and sites. Further studies are needed to assess whether pupal productivity indices may be used as epidemiological indicators of risk of dengue transmission.